(untitled) (Universal International Scientific Journal, 2026)
The training of highly qualified teachers is a priority state task, the solution of which largely determines the success of the country in the economic and socio-cultural development. The importance of teachers in the systems of general and vocational education necessitated the development of a professional standard that regulates the system of competencies and requirements necessary for the organization and implementation of professional training in various educational institutions. In this article, we will focus on these